PERAN UNIT PELAKSANAAN TEKNIS DAERAH PERLINDUNGAN PEREMPUAN DAN ANAK (UPTD PPA) DALAM PENANGANAN KEKERASAN DALAM RUMAH TANGGA (KDRT) DI KABUPATEN SIDOARJO - Dewi Fatimah; Hendra Sukmana (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2025)
Domestic violence (DV) is a human rights violation that impacts the physical, psychological, and social well-being of victims, especially women. This study aims to analyze the role of the Regional Technical Implementation Unit for the Protection of Women and Children (UPTD PPA) of Sidoarjo Regency in handling domestic violence cases. The approach used was descriptive qualitative with data collection techniques through observation, interviews, and documentation studies. The results show that UPTD PPA carries out three main roles: as a regulator in forming regulations and SOPs; as a facilitator providing facilities, infrastructure, and psychological and legal services; and as a coordinator in establishing synergies with various parties. However, challenges remain, such as limited resources and low public awareness. This study recommends improving inter-agency coordination and strengthening human resources for effective handling of domestic violence.